BlsA Is a Low to Moderate Temperature Blue Light Photoreceptor in the Human Pathogen Acinetobacter baumannii - Golic, Adrián E.; Valle, Lorena; Jaime, Paula C.; Álvarez, Clarisa E.; Parodi, Clarisa; Borsarelli, Claudio D.; Abatedaga, Inés; Mussi, María Alejandra (Frontiers in Microbiology, 2019)
Light is an environmental signal that produces extensive effects on the physiology of the human pathogen Acinetobacter baumannii. Many of the bacterial responses to light depend on BlsA, a bluelight using FAD (BLUF)-type photoreceptor, which also integrates temperature signals. In this work, we disclose novel mechanistic aspects of the function of BlsA. First, we show that light modulation of motility occurs only at temperatures lower than 24°C, a phenotype depending on BlsA. Second, blsA transcript levels were significantly reduced at temperatures higher than 25°C, in agreement with BlsA protein levels in the cell which were undetectable at 26°C and higher temperatures. Also, quantum yield of photo-activation of BlsA (lBlsA) between 14 and 37°C, showed that BlsA photoactivity is greatly compromised at 25°C and absent above 28°C. Fluorescence emission and anisotropy of the cofactor together with the intrinsic protein fluorescence studies suggest that the FAD binding site is more susceptible to structural changes caused by increments in temperature than other regions of the protein. Moreover, BlsA itself gains structural instability and strongly aggregates at temperatures above 30°C. Overall, BlsA is a low to moderate temperature photoreceptor, whose functioning is highly regulated in the cell, with control points at expression of the cognate gene as well as photoactivity.